COMPARISON OF OUTCOME OF 1- AND 2-KNOT, 4-STRAND, DOUBLE-MODIFIED KESSLER FLEXOR TENDON REPAIR WITH EARLY ACTIVE MOBILIZATION PROTOCOL IN PATIENTS WITH FLEXOR TENDON LACERATIONS OF HAND - Mujahid, Abdul Malik; Saleem, Muhammad; Ahmadi, Shohreh; Khalid, Farrukh Aslam; mehrose, Muhammad younas; Yousaf, Muhammad Ameen; Abidin, Zain Ul; Tarar, Moazzam Nazeer (Journal of Ayub Medical College Abbottabad, 2018)
Background: Hand is unique for the dexterity of its function and flexor tendons have most important function in hand. Its injury is a challenging treatment. Purpose of this study is to compare the success of 1- and 2-knot, flexor tendon repair (good to excellent results) with early active mobilization in terms of total active motion (TAM) of affected hand postoperatively. Methods: Hundred patients with age range of 5-70 years of age presenting with flexor tendon lacerations of hand were included in the study. Subjects were randomly divided into Group A, who underwent flexor tendon repair using 4 strands of double modified Kessler repair with 1 knot and Group B, in which 4 strand double modified Kessler repair with 2 knot technique was used. All patients followed early active motion protocol started in first 48 hours. They were followed at 3, 6 and 8 weeks after surgery for TAM. Data was entered and analysed in SPSS ver: 21.0. Frequency and percentages were calculated for outcome of procedure. Results: In group A 89.8% (44) of patients had good to excellent results in terms of total active motion (TAM) as compared with 90.9% (40) in group B using early active mobilization protocol. Conclusion: The study concluded that that four strand double modified flexor tendon repair using either 1 or 2 knot technique are excellent choices of repair with early active mobilization protocols. Keywords: Flexor tendon injuries; 4 strand repair; Total active motion; Early active mobilization